Atmospheric circulation patterns associated with monthly and daily temperature and precipitation extremes in Alaska - Bieniek, Peter A.; Walsh, John E. (International journal of climatology, 2017)
ABSTRACT This study presents (1) the temporal variations and trends of monthly and daily temperature and precipitation extremes in Alaska, and (2) the synoptic‐scale circulation patterns associated with these extremes. The analysis is based on daily station observations of maximum temperature, minimum temperature and precipitation from 1948–2012 as well as monthly average temperatures and precipitation from 1920–2012 from 13 Alaska climate divisions. The frequencies of daily and monthly temperature extremes show variability and trends over the past 50–90 years consistent with a warming climate in Alaska. This warming is superimposed on low‐frequency variability attributed to the Pacific Decadal Oscillation. Unlike the temperature extremes, occurrences of heavy‐precipitation extremes do not display a coherent signal through time. The changes do not appear to be linked with an overall increase in the variance of temperature or precipitation. Composite analysis of sea level pressure (SLP) anomalies associated with a representative sample of different daily and monthly temperature extremes across Alaska shows that temperature and moisture advection, subject to topographic and coastal influences, is a key driver of these events. Composite SLP fields for daily and monthly extremes are similar, especially in winter, indicating that monthly extremes represent the recurrence of daily extreme patterns during those extreme months. The SLP anomalies were also often reduced in magnitude in the summer events compared with winter, consistent with the lower variance of temperature and SLP during summer.